INFLUENCE OF RENAL ULTRASONOGRAPHIC FINDINGS ON GFR DURING CHRONIC UNILATERAL OBSTRUCTION IN DOGS - S. G. Bokhari; J. Hou; M. Iqbal; Y. Wu; Y. Wang (Journal of Animal and Plant Sciences, 2012)
Renal sonographic findings can now be implicated for prediction of changes in Glomerular filtration rate, and estimation of the degree of renal dysfunction in pets. This was successfully determined during a 20-day chronic unilateral ureteral obstruction in experimental dogs. GFR was quantitatively measured following a single intravenous bolus of inulin. The total clearance of the marker was calculated from the decrease in serum concentrations using a two-compartment model. Changes in renal architecture (i.e. length, width, depth, cortex, pelvis and ureteral dilation) were simultaneously assessed using B-mode ultrasonography. The results showed significant changes in GFR and renal architecture. Statistical analysis revealed minimum intragroup variance in renal length, width and depth. Linear regression analysis indicated a highly significant average correlation coefficient (r) with low standard error of estimates (SEE) and greater predictability between GFR and left renal dimensions of length (r=-0.9454, SEE= 2.64), width (r= -0.8632, SEE= 1.69), depth (r=-0.9461, SEE= 2.11), pelvis (r=-0.9035, SEE= 3.91) and left ureter (r=-0.9714, SEE= 2.07). The prediction error was about 9-12%. Conclusively, ultrasonographic changes in renal dimensions, particularly renal length, width and depth may successfully be used in dogs for prediction of changes in GFR, without the need to perform complicated laboratory procedures in future.
Keywords: ureteral obstruction; GFR; ultrasonography; dogs